2004
DOI: 10.1002/art.20320
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of interleukin‐18 binding protein production by blood and synovial cells from patients with rheumatoid arthritis

Abstract: Objective. To study the regulation of interleukin-18 binding protein (IL-18BP) production by rheumatoid arthritis (RA) or control peripheral blood mononuclear cells (PBMCs) and by RA synovial tissue cells, and to compare the levels of IL-18BP messenger RNA (mRNA) expression in whole blood from RA patients and controls.Methods. Unstimulated or phytohemagglutinin and phorbol myristate acetate (PHA/PMA)-stimulated PBMCs from 10 RA patients and 12 healthy controls and unstimulated or PHA/PMA-stimulated synovial ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
2
7
0
1
Order By: Relevance
“…The reduced IL-18BP mRNA expression in PBMCs from RA patients may in turn enhance the IL-18 bioactivity, leading to the proinflammatory profile characteristic of RA. In line with our results, Kawashima et al (2004) have reported recently that unstimulated whole blood samples from RA patients showed lower levels IL-18BP mRNA expression (by RT-PCR) than those from healthy controls. In our previous study, we have observed significant levels of IL-18 in the serum samples of RA patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The reduced IL-18BP mRNA expression in PBMCs from RA patients may in turn enhance the IL-18 bioactivity, leading to the proinflammatory profile characteristic of RA. In line with our results, Kawashima et al (2004) have reported recently that unstimulated whole blood samples from RA patients showed lower levels IL-18BP mRNA expression (by RT-PCR) than those from healthy controls. In our previous study, we have observed significant levels of IL-18 in the serum samples of RA patients.…”
Section: Discussionsupporting
confidence: 93%
“…Cytokines play important roles in various pathophysiological processes in human. Thus, quantification of cytokine mRNA levels are potentially useful as sensitive markers for determination of the state of immune cell activation (Kawashima et al, 2004). Moreover, the sequential determination of cytokine mRNA patterns could become a valuable tool for monitoring patients and improving therapy in a variety of clinical settings such as infectious diseases, autoimmune disorders or organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we detected the levels of IL-18BP in synovial fluid, serum, and IL-18BP expression in synovial tissue. We found that IL-18BP decreased in serum, synovial fluid, and synovial tissue along with the increases of IL-18 and IFN-c. An in vitro study [34] indicated that production of IL-18BP did not increase without stimulation of IL-12 in the culture supernatants of PBMCs and synovial tissue from RA patients. As a constitutively secreted protein, IL-18BP is able to bind IL-18 with high affinity, providing a potential mechanism whereby IL-18 activity could be regulated.…”
Section: Discussionmentioning
confidence: 99%
“…При РА ИЛ 18 обнаруживается в синовиальной обо-лочке сустава и синовиальной жидкости, причем высокий уровень в очаге воспаления ассоциируется со снижением его продукции мононуклеарными клетками перифериче-ской крови [40]. Повышение уровня ИЛ 18 коррелирует с активностью заболевания.…”
Section: ц и т о к и н ы с е к р е т и р у е м ы е T H 1 -и T H 2 -unclassified